Is heart failure associated with worse outcomes in patients admitted with pneumonia – nationwide analysis. (14th October 2021) - Arif, A W; Murthi, M; Mehdi, S A; Yadav, N
Abstract: Background: Heart failure (HF) constitutes a huge public health burden today with acute respiratory infections being among the main precipitating causes for hospitalization. On the other hand, HF is a known risk factor for pneumonia which is the most common cause of adult hospital admissions in the United States. Objective: To examine the effect of HF on the in-hospital outcomes of pneumonia Methods: The National Inpatient Sample (NIS) database, 2016–2018, was queried for inpatient principal diagnosis of all-cause pneumonia, and the study group was stratified into those with and without HF as a secondary diagnosis, using International Classification of Diseases-10 (ICD-10) codes. Multivariate logistic and linear regression analyses were used to adjust for confounding. Stata 16 software was used for data analysis. Results: 1, 929, 598 adults were hospitalized with the primary diagnosis of pneumonia, of which 499, 740 (25.9%) had HF. The incidence of mortality was 4.2% (n=20, 785) in those with HF compared to 2.0% (n=28, 365) in those without HF. The adjusted odds ratio (aOR) of inpatient mortality for pneumonia patients with HF compared to those without HF was 1.35 (95% CI, 1.29–1.42; p<0.001) when adjusted for patient demographics, comorbidities, and hospital characteristics. The adjusted hospital length of stay (LOS) in pneumonia patients with HF as compared to those without HF (mean difference= +1.40 days, p<0.001) was significantly longer. Complications such as arrhythmias (aOR=3.18; 95% CI, 3.12–3.25; p<0.001), acute hypoxic respiratory failure (aOR=1.26; 95% CI, 1.24–1.29; p<0.001), acute kidney injury (aOR=1.34; 95% CI, 1.31–1.37; p<0.001), septic shock (aOR=1.60; 95% CI, 1.41–1.81; p<0.001), cardiogenic shock (aOR=7.40; 95% CI, 5.65–9.65; p<0.001) and cardiac arrest (aOR=1.91; 95% CI, 1.71–2.14; p<0.001) were more common in pneumonia patients with HF than those without HF. Conclusion: In patients hospitalized for pneumonia, HF is associated with increased odds of inpatient mortality and longer LOS. Complications such as arrhythmias, acute hypoxic respiratory failure, acute kidney injury, septic shock, cardiogenic shock and cardiac arrest occur more frequently in pneumonia patients with HF. Funding Acknowledgement: Type of funding sources: None.